Is Thermogravimetry an efficient alternative to gas chromatography in degree of biodiesel conversion? - Gaglieri, Caroline [UNESP]; Alarcon, Rafael T. [UNESP]; de Moura, Aniele [UNESP]; Mendes, Roni A.; Caires, Flávio J. [UNESP] (Springer Nature, 2018)
This work aims to determine if thermogravimetry could be used to determine the degree of conversion of soybean oil to biodiesel without knowing the amount of ester in the sample, comparing the results with the values obtained by the standard method, gas chromatography. The syntheses were made using homogeneous and heterogeneous catalysts, and the measures were made in triplicate on both pieces of equipment. The average values (%) obtained were 74.59 ± 0.58, 66.5 ± 1.62, 13.54 ± 0.32 by thermogravimetry and 74.09 ± 0.46, 62.08 ± 2.19, 17.07 ± 0.31 by gas chromatography. These data were statistically compared using F-test, and the result indicated that the thermogravimetry could be used as analytical technique to determine the degree of conversion of biodiesel, with the same reliability as gas chromatography. The thermogravimetry shows more advantages than gas chromatography, because it does not require organic solvent, following the Green Chemistry Principles, and it is already used to determine other thermal properties of biodiesel.
Keywords: Biodiesel; Degree of conversion; Gas Chromatography; Green Chemistry; Thermogravimetry